The Influence of Direct and Indirect Juvenile Victimization Experiences on Adult Victimization and Fear of Crime. (November 2015) - Grubb, Jonathan A.; Bouffard, Leana A.
Research has identified that juvenile victimization can play a detrimental role for individuals later in life. While this literature has focused on direct and indirect forms of victimization at different stages of life, the influence of juvenile victimization on fear of crime and violent victimization as an adult has been limited. To expand this body of literature, the present research examines the effects of direct (sexual victimization) and indirect (witnessing parental intimate partner violence) juvenile victimization on fear of crime as well as the prevalence of victimization as an adult. Using telephone survey data collected from randomly selected Texas adults, this study demonstrates that both juvenile sexual victimization and indirect victimization increase the likelihood of adult victimization, whereas juvenile sexual victimization increases the likelihood of adult sexual victimization. In contrast, fear of crime as an adult was not significantly influenced by either juvenile sexual victimization or indirect victimization. A discussion of how these findings relate to previous research, limitations, and implications are also provided.